Tendencias e impacto de la inteligencia artificial en comunicación: cobotización, gig economy, co-creación y gobernanza - Dr. José Miguel TÚÑEZ LÓPEZ (Fonseca, Journal of Communication, 2023)
This article reviews the scientific production on the impact of technology on communication management, in a global way, and the identification of changes and trends due to the application of AI, in a more concrete way. It is an interpretative research that works on a purposive sample created from search results in Google Scholar, WoS and Scopus, limited to a longitudinal period of five years (2016 to 2020).